2021
DOI: 10.1128/spectrum.00644-21
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus nidulans AmyG Functions as an Intracellular α-Amylase to Promote α-Glucan Synthesis

Abstract: Short α-1,4-glucan was suggested as the primer structure for α-glucan synthesis. However, the exact structure and its source remain elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The primer maltooligosaccharides, which are likely required for a-1,3-glucan biosynthesis, are predicted to be produced by AmyG (He et al, 2014;Miyazawa et al, 2018;Miyazawa et al, 2020). Kazim et al (2021) reported that, under submerged culture conditions, amyG disruption in A. nidulans causes the formation of dispersed hyphae and decreases pellet size and a-1,3-glucan content in the cell wall in comparison with the parental strain; these changes can be reverted by adding maltose or maltotriose to the culture media, suggesting that AmyG provides maltooligosaccharides for a-1,3-glucan biosynthesis. Chemical analyses of cell wall a-1,3-glucan in A. nidulans (Miyazawa et al, 2018) and Aspergillus wentii (Choma et al, 2013) revealed concatenation of a subunit consisting of about 200 a-1,3linked glucose residues and a spacer of several 1,4-linked glucose residues.…”
Section: Introductionmentioning
confidence: 99%
“…The primer maltooligosaccharides, which are likely required for a-1,3-glucan biosynthesis, are predicted to be produced by AmyG (He et al, 2014;Miyazawa et al, 2018;Miyazawa et al, 2020). Kazim et al (2021) reported that, under submerged culture conditions, amyG disruption in A. nidulans causes the formation of dispersed hyphae and decreases pellet size and a-1,3-glucan content in the cell wall in comparison with the parental strain; these changes can be reverted by adding maltose or maltotriose to the culture media, suggesting that AmyG provides maltooligosaccharides for a-1,3-glucan biosynthesis. Chemical analyses of cell wall a-1,3-glucan in A. nidulans (Miyazawa et al, 2018) and Aspergillus wentii (Choma et al, 2013) revealed concatenation of a subunit consisting of about 200 a-1,3linked glucose residues and a spacer of several 1,4-linked glucose residues.…”
Section: Introductionmentioning
confidence: 99%
“…The primer maltooligosaccharides, which are likely required for α-1,3-glucan biosynthesis, are predicted to be produced by AmyG (He et al, 2014;Miyazawa et al, 2018Miyazawa et al, , 2020. Kazim et al (2021) reported that, under submerged culture conditions, amyG disruption in A. nidulans causes the formation of dispersed hyphae and decreases pellet size and α-1,3-glucan content in the cell wall in comparison with the parental strain; these changes can be reverted by adding maltose or maltotriose to the culture media, suggesting that AmyG provides maltooligosaccharides for α-1,3-glucan biosynthesis. Chemical analyses of cell wall α-1,3-glucan in A. nidulans (Miyazawa et al, 2018) and Aspergillus wentii (Choma et al, 2013) revealed concatenation of a subunit consisting of about 200 α-1,3-linked glucose residues and a spacer of several 1,4-linked glucose residues.…”
Section: Introductionmentioning
confidence: 99%
“…The primer maltooligosaccharides, which are likely required for α-1,3-glucan biosynthesis, are predicted to be produced by AmyG (He et al, 2014; Miyazawa et al, 2018, 2020). Kazim et al (2021) reported that, under submerged culture conditions, amyG disruption in A. nidulans causes the formation of dispersed hyphae and decreases pellet size and α-1,3-glucan content in the cell wall in comparison with the parental strain; these changes can be reverted by adding maltose or maltotriose to the culture media, suggesting that AmyG provides maltooligosaccharides for α-1,3-glucan biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The GH13_5 subfamily was initially found in bacteria as liquefying αamylases (Janíčková & Janeček, 2020) breaking down starch polymers but they do not produce free sugars (Mehta et al, 2016). In fungi, some intracellular GH13_5 amylases with AmyAc_AmyA-domain (with or without DUF1939-domain) were recently classified as to be involved in the synthesis of cell wall α-1,3-glucan (Marion et al, 2006;Yoshimi et al, 2017;Janíčková & Janeček, 2020;Kazim et al, 2021; see below).…”
Section: *Weak Signalmentioning
confidence: 99%
“…In fungal cell wall α-1,3-glucan biosynthesis, the extracellular AmyAc_AGS domain in the respective α-1,3gucanases is supposed to crosslink different α-1,3-glucan chains by transglycosylation (Yoshimi et al, 2017). Interestingly, in some Ascomycetes such as Aspergillus species, gene clusters of AGS (EAA63275) and two α-amylase-genes AmyD (EAA63276.1) and AmyG (EAA63277.1) (names as used in Aspergillus nidulans; Yoshimi et al, 2017) were described in the literature for concerted α-glucan synthesis by Ags together with the intracellular AmyG of the GH13_5 subfamily (see above) that provides as precursor maltose by hydrolysis of maltooligosaccharides (He et al, 2014;Yoshimi et al, 2017;Kazim et al, 2021) and under C-starvation conditions again its degradation by activity of secreted and GPI membrane-anchored GH13_1 AmyD (containing AmyA + DUF1966; see below) in order to release oligosaccharides or glucose for import into the cells and use as C-source (van der Kaaij et al, 2007;He et al, 2017;Yoshimi et al, 2017).…”
Section: *Weak Signalmentioning
confidence: 99%